The role of Adipocytokines, Vitamin D, and C in Colorectal Cancer - Akam Jasim Mustafa; Hazhar M. Balaky; Parween Abdulsamad Ismail (Baghdad Science Journal, 2023)
Colorectal cancer is the world's 3rd most frequent malignant neoplasm and the 4th most common cancer in Iraq. Leptin and Adiponectin are two major Adipocytokines produced by adipose cells that have opposite effects on the formation of colorectal tumors. Leptin induces tumor growth and metastasis, whereas Adiponectin inhibits it. 1,25-Dihydroxyvitamin D controls and limits cancer cell proliferation, differentiation, and survival. Vitamin C deficiency, on the other hand, has been regularly detected in cancer tissues and has potent anti-cancer properties. The purpose of this study was to look at the biochemical role of circulatory Adipocytokine levels (Adiponectin and Leptin) as well as the anti-cancer potentials of Vitamin D and C in CRC patients from Iraq. The research looked at confirmed cases of CRC who were seen at Nanakali Hospital for Blood diseases and Cancer in Erbil before their treatment sessions. A total of 35 patients with confirmed CRC cases and 36 healthy participants who were age, gender, and BMI matched were recruited. ELISA technique was used to quantify serum levels of Adiponectin, Leptin, Vitamin D, & C. The results showed a significant increase (P<0.0001) of serum Adiponectin levels (12.06±1.59) in CRC patients relative to the controls (2.05±0.96). On the contrary, the serum Leptin levels (24.09±2.92) were non-significantly lower (P=0.098) in CRC patients in comparison to controls (53.84±1.54). Furthermore, serum Vitamin D (13.14±1.21) and Vitamin C (1.03±0.10) levels in CRC patients were significantly lower (P<0.0001) when compared to controls (24.49±1.47, 5.78±2.16), respectively. The findings in the current study suggest an imperative biochemical role of Adipocytokines (Adiponectin and Leptin) and Adipose tissue dysfunction in the pathogenesis of CRC patients. Furthermore, decreased serum levels of Vitamin D and C reduce their effective anti-cancer effects, allowing Colorectal malignant neoplasms to survive and develop. Thus, the present study findings suggest Adiponectin and Leptin as potent prognostic and risk factors of CRCs. Also, Vitamin D and C deficiencies are the major risk factors among Iraqi CRC patients.